Climate change is leading to an ecological trap in a migratory insect - Shi-Yan Zhang; Yi-Yang Zhang; Fan Yang; Chen Zhou; Hui-Mei Shen; Bei-Bei Wang; Juan Zeng; Don R. Reynolds; Jason W. Chapman; Gao Hu (Proceedings of the National Academy of Sciences, 2025)
Many insect migrants rely on favorable seasonal winds to carry out long-range latitudinal migrations. In East China, the annual advance and retreat of the East Asian summer monsoon produces ideal conditions for seasonal range expansion and contraction of many migratory crop pests. However, climate-induced changes in the strength, timing, and location of the monsoon are impacting wind systems which may, in turn, affect migration patterns. We investigated these questions in the rice leafroller (RLR) moth, a severe pest of rice that annually invades the Lower Yangtze River Valley (LYRV) of China from winter-breeding areas further south. Using a 24-y dataset of RLR population dynamics from 31 monitoring stations across Southeast China, we investigated the impact of changes in monsoon wind regimes on fall migration patterns of the pest. Historically, RLR emigrated from the LYRV to South China on the favorably directed winds produced by the retreat of the monsoon at the end of the outbreak season (from mid-August onward). We show that in the recent 12-y period, prevailing late-season winds remain northward for longer than previously, preventing locally produced moths from emigrating southward. Additionally, winds now facilitate mass late-season immigrations into the LYRV, creating an ecological trap, as immigrants do not have time to produce another generation. As a consequence of the changing wind patterns, pest pressure is declining, and climate-induced changes to the East Asian summer monsoon result in seasonal migration becoming a riskier strategy. Such changes in insect migration patterns have severe implications for the population dynamics of windborne migrants, ecosystem functioning, and pest management strategies.